Bacteriological Findings within Internal Implant Hole Following Flapless Implant Placement - Khudair A Abd; Basima G Ali; Abbas S AL-Mizraqchi (College of Dentistry/ University of Baghdad, 2018)
Back ground: Microbial penetration inside the implant's internal hole creates a bacterial reservoir that is related with an area of inflamed connective tissue opposite the fixture-abutment junction and this can affect the health of the peri-implant tissue. Aims of the study: Evaluate the types aerobic and anaerobic bacterial count-percentage and difference between Aerobic and Anaerobic microflora in the implant screw hole three months after implant placement. Monitor the periodontal health status of all patients, throughout the study. Material and methods: Study methodology; Eight partially edentulous patients received 20 dental implants and these implants done with flapless surgical procedure. All patients examined clinically to determined their oral health status by examination of their plaque index, Gingival index and Bleeding on probing, each two weeks for 90 days (8visits) throughout the study period. Three months after that, the plaque sample collected from the internal hole of fixture and transfer to bacterial investigation and assessment the amount of anaerobic and aerobic bacteria. Results: Although the anaerobic viable count is higher than that of aerobic, but with statistically not significant difference between those counts (P>0.05). Keywords: screw hole, flapless surgical implant placement, bacterial count, Aerobic and Anaerobic bacteria